(untitled) (Medical Forum Monthly, 2025)
Objective: Researchers examined acute febrile illness (AFI) manifestations together with laboratory test results from patients visiting a tertiary care facility in Karachi. Study Design: Descriptive Cross-Sectional study Place and Duration of Study: This study was conducted at the Dr. Ruth KM Pfau Civil Hospital together with Dow University Hospital in Karachi. Start of study October 2022 completion July 2023. Methods: Researchers studied a population of 300 adults between 20 and 70 years old with fever duration between 3 and 14 days. The data collection included patient demographics along with symptoms and medical history in addition to CBC, LFTs, cultures, malaria/dengue tests, and radiological tests. The study utilised both descriptive and inferential analysis methods. Results: The research examined a total of 300 patients who had an average age of 38.5 years (SD: 12.4) and a female participant ratio of 58.66%. All patients experienced fever, while body aches presented in 56.33% of cases, alongside headaches in 53.3% and joint pain in 51.3%. Pallor was detected in 45.66% of patients, followed by hepatosplenomegaly in 16.33% of patients, and 12.33% presented with jaundice. Lab tests identified E. coli in 12.0% of patients, alongside Salmonella in 9.7% and dengue in 18.9%, and malaria in 22.33% of the cases. Chest scans displayed both consolidation patterns and pleural effusion in 6.3% and 3.1% of cases, showing how full diagnostic evaluation matters for AFI patients. Conclusion: Patient care in limited resource contexts requires better diagnostic systems and location-based guidelines for dengue and malaria with advanced detection methods, according to this research.